Risk of falling, fear of falling and functionality in community-dwelling older adults - Fernandes, Beatriz (2017)
Ageing among Portuguese population is leading to an increase in the proportion of elderly people. Age-related changes are responsible for high levels of disability, balance problems and high risk of falls, Physiotherapy can identify elderly in risk of falling and provide strategies to prevent falls in this population contributing to maintain functionality. The purpose of this study was to characterise the risk of falling in a sample of community-dwelling older adults and investigate the associations between functionality and balance. Objective: To identify the risk of failing in community-dwelling older adults and ifs relations with fear of falling and functional capacity.